On the role of AtDMC1, AtRAD51 and its paralogs during Arabidopsis meiosis - Pradillo, Mónica; Varas, Javier; Oliver, Cecilia; Santos, Juan L. (Frontiers in Plant Science, 2014)
Meiotic recombination plays a critical role in achieving accurate chromosome segregation and increasing genetic diversity. Many studies, mostly in yeast, have provided important insights into the coordination and interplay between the proteins involved in the homologous recombination pathway, especially the recombinase RAD51 and its meiotic paralog DMC1. Here we summarize the current progresses on the function of both recombinases, and the CX3 complex encoded by AtRAD51 paralogs, in the plant model species Arabidopsis thaliana. Similarities and differences respect to the function of these proteins in other organisms are also indicated.